Social Comparison Orientation in Monozygotic and Dizygotic Twins. (10th November 2017) - Huguet, Pascal; Carlier, Michèle; Dolan, Conor V.; de Geus, Eco J.; Boomsma, Dorret I.
Abstract : Twin research has offered evidence that monozygotic (MZ) twins are more socially close than dizygotic (DZ) twins, but has not paid much attention to the way twins compare themselves with their co-twin. The few studies in this area suggest that 'horizontal comparisons' (social comparison motivated by solidarity or communion with others) matter more for MZ twins than for DZ twins, at least when the co-twin is the social comparison standard. Consistent with this view, we predicted higher interest in MZ twins relative to DZ twins to select their co-twin rather than other people in general as the social comparison standard. The Social Comparison Orientation (SCO) scale, which measures the inclination to compare with others in a horizontal rather than vertical mode (comparing either upward or downward), was administered in 90 MZ pairs and 57 same-sex DZ pairs (63% female; average age 18.06 years) from the Netherlands Twin Register. MZ twin pairs showed significantly higher SCO scores than DZ twin pairs (with a large effect size) on the co-twin SCO, whereas the two groups did not differ from each other on the general SCO excluding the co-twin as social comparison standard. In MZ twin pairs, anxiety was associated with social comparison with others in general, not with their co-twin. For both scales, twin resemblance was explained by additive genetic variance. The present findings provide direct evidence that horizontal comparisons with the co-twin are of particular importance for MZ twins.